Chemical modification of carbon nanomaterials (SWCNTs, DWCNTs, MWCNTs and SWCNHs) with diphenyl dichalcogenides. Issue 14 (12th March 2015) - Syrgiannis, Z.; Bonasera, A.; Tenori, E.; La Parola, V.; Hadad, C.; Gruttadauria, M.; Giacalone, F.; Prato, M.
Abstract : A simple approach for the simple functionalization of different Carbon Nanoforms (CNFs) is described. Reaction with diphenyl dichalcogenides allow to tune CNFs electronic properties. Abstract : Control over chemical functionalization is a crucial point in the field of nanotechnology. Herein, we present the covalent functionalization of several carbon nanoforms (single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes and carbon nanohorns) by means of diphenyl dichalcogenides. These ones show different reactivity to the nanomaterials and are able to modify their electronic properties depending on the electronegativity of the functionalizing heteroatom. Theoretical calculations were also performed to support the experimental results. All the modified structured nanocarbons were thoroughly characterized by TGA Raman, XPS, UV/Vis/nIR, IR and TEM techniques. Our findings propose a simple approach to functionalize carbon nanomaterials and, in the meantime, to tune their electronic properties.